Rangelands and their Governance: Implications for Traditional Pastoralists - Squires, Victor R; Gaur, Mahesh Kumar; Feng, Haiying (Annals of Arid Zone, 2019)
Rangelands play an important role in the livelihood of local communities and wildlife. In this paper, however, the three main roles of rangelands in low rainfall areas will be discussed in the following sections: (i) as a feed source for livestock production; (ii) a base of survival for local communities, their institutions, and management practices they developed to overcome environmental variability; and (iii) as a means of avoiding conflicts between herders and farmers. This paper is about local communities of people who live in and get their livelihoods from drylands. On a global basis they number hundreds of millions of people with thousands of millions of livestock. The focus is on the human dimension of rangelands i.e. indigenous communities, local institutions, and resource management systems. Key words: Development, tenure, common property, privatization, traditional institutions, pastoralism.